The people’s game: evolutionary perspectives on the behavioural neuroscience of football fandom - Butler, Matt; Brar, Gurjot; Abed, Riadh; O’Connell, Henry (Frontiers in Psychology, 2025)
Association football (soccer) is the world’s most popular sport. Transculturally, fans invest significant resources following their teams, suggesting underlying psychological universals with evolutionary origins. Although evolutionary science can help illuminate the ultimate causes of human behaviour, there have been limited modern evolutionary perspectives on football fandom. In this paper, we consider evolutionary perspectives on football fandom from a behavioural neuroscientific standpoint. We discuss how the appeal of football may arise through the low-scoring and highly variable outcomes of games; we relate this to the neuroscience of reward prediction errors and motivation. We highlight recent research on the psychobiological responses to ritual, including endorphin release, which may reduce anxiety and facilitate group bonding. We discuss the prosocial and anxiety-sublimating effects of the matchday ritual and argue that football may be a special case whereby ritual behaviour does have a small effect on the outcome of interest. We discuss the psychology of ingroup and outgroup effects of fandom and argue that, although resource scarcity can sometimes lead to aggression, that larger inter-group effects can be positive. We comment on the socioemotional developmental aspects of football fandom, and note how group identification may lead to displays of sacrifice. We finish with a discussion of whether, in the era of social prescribing, football could be seen as a psychiatrist’s tool. We conclude with suggestions on how the positive aspects of football can be emphasised through evolutionary perspectives, and how future research on football fandom may inform evolutionary understanding of humans writ large.